Comparison of fluoxetine with other selective serotonin reuptake inhibitors in the treatment of premature ejaculation: A systematic review and meta‐analysis. (27th June 2022) - Liu, Qiushi; Gao, Hui; Huang, Yuanyuan; Wang, Ming; Jiang, Hui; Dai, Yutian; Zhang, Xiansheng
Abstract: The primary goal of this systematic review and meta‐analysis was to compare the efficacy and safety of fluoxetine with other oral pharmaceuticals in the treatment of premature ejaculation (PE). We searched through databases including CNKI, PubMed, EMBASE and Cochrane to find research published up to 31 March 2022. PROSPERO was used to pre‐register this meta‐analysis (registration number CRD42022315459). Two separate writers extracted relevant details from all of the papers included in the study. To analyse the quality of literature publishing, we used the Cochrane risk of bias tool. The severity of premature ejaculation was determined using intravaginal ejaculatory latency time (IELT), and the effectiveness and safety of pharmacological interventions were determined using standardized mean difference (SMD) and risk ratio (RR) values with matching 95% confidence level intervals (95% CIs). Our meta‐analysis includes a total of ten trials to investigate into the differences in treatment efficacy and safety between fluoxetine and other medicines. The findings revealed that fluoxetine was more effective than placebo in treating PE, whereas sertraline and paroxetine were more effective than fluoxetine ( p < 0.05). The side effects of the medications were not significantly different, and they were all acceptable. The results of the sensitivity analysis were unaffected by the removal of any of the articles. There was no evidence of bias in the media. This meta‐analysis examined the differences in efficacy and safety between fluoxetine and other oral medications and can be used by clinicians in the treatment of PE.